P241 Diagnostic timeline of patients with suspected malignant (unilateral) effusion in a large tertiary centre. (15th November 2017) - Crowley, L; Rajgor, A; Asa'ari, AKA Abi Musa; Yoganayagam, N; Palit, T; Ali, A; Rowe, N; Bikmalla, S; Iqbal, M; Ganaie, B; Haris, M; Cusay, T; et al.
Abstract : Introduction: Malignant pleural effusions (MPE) remain a significant problem with approximately 50% of all cancer patients developing a MPE during their disease process. Our pleural service is one of the largest in the country. This day case service has the potential to accelerate MPE diagnosis, management and thus enhance patient experience. Objectives: The aim was to assess the timeline of patients referred to pleural clinic with suspected malignant (unilateral) effusion. Method: Retrospective analysis of 178 consecutive patients referred to pleural clinic with suspected MPE from March 2015 to November 2016. Data was collated from electronic patient records, including route of referral, diagnosis methodology, speed of diagnosis (MDT) and procedures performed. Results: 126 (70.8%) of the 178 patients had pleural effusion and underwent pleural aspiration. 61 patients (48.4%) had positive malignant fluid cytology. 26 (43%) and 35 (57%) were thoracic and extra thoracic malignancies respectively. Out of the 61 patients, 26 (43%) had systemic treatment and 35 (57%) had palliative management. These patients were diagnosed on average within 17 days from referral to clinic (SD 17.3). Mean time taken from referral to pleural clinic review was 5 days (SD 6.6) and 12.3 days (SD 16.6) elapsed from pleural clinic review to diagnosis. Average time from cytology diagnoses to treatment was 26 days. 20 (16%) patients were referred for VATS (Video Assisted Thoracoscopic Surgery). The average time from VATS diagnosis to treatment was 37 days (for further breakdown see Table 1 ). The remaining (64%) were benign till to date. Conclusion: The data demonstrates that a dedicated pleural service has the ability to rapidly review and diagnose patients with suspected MPE (especially the cytology positive). There is a need for improvement in patient's timeline for those referred for VATS. Perhaps a dedicated pleural multidisciplinary meeting may help to reduce the delay and improve patient care.